2000
DOI: 10.1007/s005200050013
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on fungemia in children with cancer: analysis of 35 cases and comparison with 130 fungemias in adults

Abstract: The aim of this prospective study on fungemia in children with cancer compared with adults with cancer appearing during the last 10 years in a pediatric hospital and in national cancer institutions was to investigate risk factors, etiology, therapy, complications and outcome. Univariate analysis showed significant differences in 35 children with cancer and fungemia in comparison with 130 cases of fungemias in adults with cancer. It was found that (1) therapy with corticosteroids (40 vs 18.5%, P<0.03), (2) brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 5 publications
2
16
1
1
Order By: Relevance
“…As previously reported, fungal sepsis was strongly associated with ICU mortality (41)(42)(43). On the other hand, the relatively low mortality rate (9%) associated with Gram-negative sepsis was somewhat unanticipated.…”
Section: Discussionmentioning
confidence: 56%
“…As previously reported, fungal sepsis was strongly associated with ICU mortality (41)(42)(43). On the other hand, the relatively low mortality rate (9%) associated with Gram-negative sepsis was somewhat unanticipated.…”
Section: Discussionmentioning
confidence: 56%
“…[6][7][8][9][10][11] Similar to many other disease processes, studies of adult patients with invasive fungal infections may not be relevant in pediatric patients. 12 For example, with invasive candidiasis, there are differences in isolated Candida species and antifungal susceptibilities, 13 risk factors, 14,15 treatment, 16 and outcomes 14,17 between pediatric and adult patients. Little is known about the epidemiology, risk factors, outcome, and costs of IA in a large cohort of pediatric patients.…”
mentioning
confidence: 99%
“…C albicans fungemia was more frequent in immunocompromised adults than in children identified with other Candida species. 6,7 A review of cutaneous mold infections in pediatric patients in Houston, TX (1991TX ( -2000 showed that neonates were involved in 50% of the cases and that extremely low birth weight (ELBW) premature infants, immunocompromised hosts, and cutaneous trauma were major risk factors. 5 This study reports DCFI in 26 pediatric patients ( # 18 years old) given a diagnosis in a pediatric tertiary care center in Montreal, Quebec, Canada, and describes their clinical characteristics, the diagnostic methods used, and patient outcomes.…”
mentioning
confidence: 99%